Precautionary Principle: Perumusan Kebijakan Pengelolaan Energi Baru Terbarukan - Yustika, Anindya (Universitas Jambi, Fakultas Hukum, 2024)
The transition to new renewable energy not only produces energy that is relatively more environmentally friendly, but there are other consequences on the environment. In this case, policy makers must be careful in making the right decision regarding a particular product or legal product, because the EBT transition has the potential to endanger society as a whole, but at the same time these dangers are not widely understood until there is scientific evidence. This article examines efforts in formulating new and renewable energy management policies with an emphasis on precautionary principles to realize sustainable national legal development. This research uses a doctrinal approach or also called a normative legal approach with descriptive analysis methods. This research shows that the energy transition policy offered by the government does not touch directly on the environmental dimensions that have been detrimental to society. On the other hand, Indonesia, which is new to the concept of EBT, needs to strive to gain trust from its people, which can occur if the system offered is safe. This is done with an established legal umbrella so that the precautionary principle must be the breath in making this EBT regulation.